Desenvolvimento sustentável, direitos humanos e contradições do modo de produção capitalista - Gonçalves, Luísa Cortat Simonetti (2013)
The current developmental economic logic still shares many of the premises of the classical economic school, which are often referred to as the great causes of the serious crises that have passed and gone through capitalism. The present work seeks, from the materialistic dialectic methodology, to present the proposals of sustainable development and, confronting them with the challenges that need to be overcome from the social, environmental and economic point of view, to analyze to what extent these proposals prove viable for the overcoming of the current crisis of capitalism. To this end, the criticisms of Zizek and Hart serve as a starting point, moving away from the state and the law, based on Agamben, and also from the removal of the solution from civil society, in that despite the contributions of Herrera Flores, to arrive at the centrality of the action of the corporations. According to the conclusions of this study, in spite of the great importance of action from the social and governmental spheres, it is not enough if integrated and effectively sustainable corporate actions can not be expected, in line with the Sukhdev.